1996
DOI: 10.1007/bf01979919
|View full text |Cite
|
Sign up to set email alerts
|

Microbial populations, fungal species diversity and plant pathogen levels in field plots of potato plants expressing theBacillus thuringiensis var.tenebrionis endotoxin

Abstract: The environmental release of genetically engineered (transgenic) plants may be accompanied by ecological effects including changes in the plant-associated microflora. A field release of transgenic potato plants that produce the insecticidal endotoxin of Bacillus thuringiensis var. tenebrionis (Btt) was monitored for changes in total bacterial and fungal populations, fungal species diversity and abundance, and plant pathogen levels. The microflora on three phenological stages of leaves (green, yellow and brown)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…after the amendments of organic fertilizers contributed to disease suppression. Consequently, microbial diversity was not always effective to independently predict soil health (Donegan et al 1996), while microbial community diversity in combination with community composition, especially for the functional microbial consortia, could be a more meaningful measure.…”
Section: Introductionmentioning
confidence: 98%
“…after the amendments of organic fertilizers contributed to disease suppression. Consequently, microbial diversity was not always effective to independently predict soil health (Donegan et al 1996), while microbial community diversity in combination with community composition, especially for the functional microbial consortia, could be a more meaningful measure.…”
Section: Introductionmentioning
confidence: 98%
“…Most studies have suggested that Bt plants cause only minor changes in the structure of microbial communities in soil, and the changes are often transient [159][160][161][162][163]. Other studies have shown no apparent deleterious effects of Cry proteins released by Bt plants in root exudates or from biomass of Bt plants incorporated into soil on microbial communities or representative enzymes [29,70,72,81,115,117,126,[164][165][166][167][168][169].…”
Section: In Situ Field Studies Of Microbial Populations and Enzyme Acmentioning
confidence: 99%
“…For example, a significant, but transient, increase in the populations of culturable bacteria and fungi was found in soil microcosms amended with leaves of Bt cotton expressing the Cry1Ac protein [161]; minimal differences were observed in the populations of culturable aerobic bacteria and fungi in soil with transgenic Bt potato expressing the Cry3A protein [162]; populations of nematodes were higher in soil with transgenic tobacco expressing protease inhibitor I than with nonmodified tobacco [192]; and significantly higher levels of culturable aerobic spore-forming and cellulose-utilizing bacteria and lower enzymatic activity of dehydrogenases and alkaline phosphatases were found in soils with transgenic alfalfa expressing -amylase or lignin peroxidase [193]. Wu et al [167,168] found that decomposing straw of Bt rice containing the Cry1Ab protein was not toxic under laboratory conditions to a variety of culturable microorganisms in a flooded paddy soil.…”
Section: In Situ Field Studies Of Microbial Populations and Enzyme Acmentioning
confidence: 99%
“…However, the specificity of its toxicity, and the rapid breakdown of proteins in the environment (compared to the ubiquitous anti-herbivore plant secondary compounds, including lignins) should make these effects relatively minor (Donegan et al 1996, National Research Council 2000. The impacts would be likely to be far less than from plantation establishment itself (compared to either a wild forest or agricultural use), or from planting of a different species or clones-as discussed above with respect to WM.…”
Section: Insect Resistancementioning
confidence: 99%